Revolution and Legal Order (to the Problem of Legitimation of the New Political Regimes) - M. A. Isaev (Московский журнал международного права)
Shocks that have been provoked by the revolution often change political and legal order in the countries undergone revolutionary collapse. One of the results of the revolution is the problem of legitimation of the new political regime. In practice the issues of recognition of the new state in international affairs. The present article analyses typology of revolution as political and legal phenomenon; it also examines possible ways of legitimation of the new state power.